2018
DOI: 10.1155/2018/8608497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorogenic Acid Intake on Cognitive Function in the Elderly: A Pilot Study

Abstract: Objective To evaluate the effect of chlorogenic acids (CGAs) intake on cognitive function. Methods In this pilot study, the Cogstate and CNS Vital Signs test batteries were used to evaluate cognitive function in 8 healthy elderly men and women complaining of subjective memory loss after a 6-month intake of a test beverage containing 330 mg of CGAs just before bedtime. Results After a 6-month CGA intake period, significant improvement was observed in the One Back Test of the Cogstate, the Shifting Attention Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 33 publications
4
36
0
1
Order By: Relevance
“…We recently reported that a continuous intake of CGA (300 mg/day) for 4-6 months improved cognitive function, especially attention and executive function, in middle-aged and elderly populations [15,16]. This study conducted a randomized controlled trial to clarify the potential for patients with MCI.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that a continuous intake of CGA (300 mg/day) for 4-6 months improved cognitive function, especially attention and executive function, in middle-aged and elderly populations [15,16]. This study conducted a randomized controlled trial to clarify the potential for patients with MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeoyl-, dicaffeoyl-and feruloyl-quinic acids from coffee improved some cognitive functions in healthy participants (n = 38) when taken for 16 weeks in an RCT (Saitou et al, 2018). A similar combination of these polyphenols also improved some memory functions in elderly subjects with cognitive decline (n = 6) when taken for 6 months in a small pilot study (Kato, Ochiai, Kozuma, Sato, & Katsuragi, 2018). A minor coffee component is eicosanoyl-…”
Section: Tea Coffee and Cocoamentioning
confidence: 99%
“…Caffeoylquinic acids including chlorogenic acid -Suppress Aβ plaque deposition and prevent associated cognitive dysfunction in an AD model (Ishida et al, 2019) Caffeoyl-,dicaffeoyl-,and feruloyl-quinic acids -Improved some cognitive functions in healthy participants (n = 38; 16 weeks) in an RCT (Saitou et al, 2018) -Improved memory functions in elderly with cognitive decline (n = 6; 6 months; Kato et al, 2018) Coffee (see above)…”
Section: Coffeementioning
confidence: 99%
“…They observed that coffee drinkers at midlife had lower risk of dementia and AD later in life compared with those drinking no or only little coffee. Kato et al [121] reported that six-month intake of CGAs improved attentional, executive, and memory functions in the elderly with complaints of subjective memory loss. It is interesting to note that CGAs may improve some of the cognitive functions included in the CNS Vital Signs (Cognitrax) score, such as motor speed, psychomotor speed, and executive functions, in healthy individuals [122].…”
Section: Rats Caffeic Acidmentioning
confidence: 99%